UPAYA MENINGKATKAN PENNJUALAN BATIK JEMBER MELALUI BRANDING JFC - Yuris Maulana Akhmad (UNEJ e-Proceeding)
Batik Jember city also developed to be used as one of the area's identity. Although less famous Jember batik with batik-batik in Java batik is actually in this area has existed since the time of the Dutch East Indies. The purpose of this study is: To know and explore the riches of jember batik, batik jember To see the potential, to analyze the fundamental problems faced by batik entrepreneurs jember, To analyze the fundamental problems faced by batik entrepreneurs jember, to determine the contribution of JFC in increasing turnover batik Jember. This research is a qualitative descriptive study that describes the phenomenon in depth. This study uses primary data is the result of interviews with key people associated with the object of research. The results showed Batik Jember excavated from local wisdom that is inspired by the town of Jember commodities featured in the tobacco and cocoa industries Kebradaan Batik Jember able to increase revenues, especially those working in the batik industry. JFC proven to be a branding for the town of Jember. People know Jember not only as a producer of tobacco and cocoa, but as a city of world-class carnival.